SYNTHESIS AND BONDING ANALYSIS OF MAGNETITE (Fe3O4)/SILICA (SiO2) COMPOSITE BASED ON SUGARCANE BAGASSE - H. Ardiyanti; D. Puspitarum; O. F. Maryana; W. A. Pujakesuma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
This article reports the results synthesis of composite Fe3O4/SiO2 and nanoparticles from natural resources (sugarcane bagasse). The synthesis of Fe3O4 and SiO2 nanoparticles used co-precipitation and sol-gel methods with SiO2 from sugarcane bagasse as a template. The XRD data analysis presented that Fe3O4 were successfully produced using co-precipitation methods. The XRD data analysis also presented that the crystalline phases showed Fe3O4. FTIR spectra presented some absorption peaks of new functional groups indicating the existence of Si-O-Si (silanol), Fe-O, and Fe-O-Si as new functional groups.